Sofosbuvir/Velpatasvir for the treatment of Hepatitis C Virus infection - Zignego, Anna Linda; Monti, Monica; Gragnani, Laura (Acta Biomedica Atenei Parmensis, 2018)
Hepatitis C Virus (HCV) infection is major health problem worldwide, with 150 million infected people according to recent epidemiologic estimations. The introduction of direct-acting antivirals made a revolutionary change in the management of HCV infected patients with surprisingly high rates of antiviral response, improved tolerability and reduced time of treatment. Sofosbuvir, in combination with different partner drugs, has been the molecule that led this incredible change. The last generation of SOF-based regimens, namely Sofosbuvir/Velpatasvir, represents a single tablet, once a day, pangenotypic and pan-fibrotic combination, demonstrated to be safe and effective in almost all type of HCV infected individuals. This review overviews the main clinical data of SOF/VEL registration trials, underlying the key features of this combination in terms of efficacy, safety and Patients Reported Outcomes obtained in more than 1800 HCV chronically infected subjects.